CRIMINAL LIABILITY FOR PERPETRATORS OF AGGRAVATED THEFT: AN ANALYSIS OF DECISION NUMBER 157/PID.B/2025/PN BTA - I Ketut Seregig; Rachmat Fadhil Pradhana (RADJA PUBLIKA, 2026)
Aggravated theft remains a persistent conventional crime that harms individuals and disrupts public order. This study examines the factors contributing to aggravated theft and evaluates the criminal liability of the perpetrator in Decision Number 157/Pid.B/2025/PN Bta. The research applies normative and empirical legal approaches. Primary data were obtained through interviews with an investigator of the East OKU Police, a public prosecutor at the East OKU District Prosecutor's Office, and a judge of the Baturaja District Court, while secondary data were collected from legislation, judicial decisions, legal scholarship, and relevant journal articles. The data were processed through editing, classification, and systematization and were then analyzed qualitatively. The findings show that the offense was influenced by the social environment, social interaction and communication, the learning of criminal techniques, economic motives accompanied by rationalization, and the dominance of definitions favorable to lawbreaking. These factors are consistent with Sutherland's differential association theory. The defendant was criminally liable because the elements of the offense, fault, capacity for responsibility, and absence of excuses were established. The court imposed two years' imprisonment.